2008
DOI: 10.1186/1742-4690-5-79
|View full text |Cite
|
Sign up to set email alerts
|

RNA silencing and HIV: A hypothesis for the etiology of the severe combined immunodeficiency induced by the virus

Abstract: A novel intrinsic HIV-1 antisense gene was previously described with RNA initiating from the region of an HIV-1 antisense initiator promoter element (HIVaINR). The antisense RNA is exactly complementary to HIV-1 sense RNA and capable of forming approximately 400 base-pair (bp) duplex RNA in the region of the long terminal repeat (LTR) spanning the beginning portion of TAR in the repeat (R) region and extending through the U3 region. Duplex or double-stranded RNA of several hundred nucleotides in length is a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 105 publications
(179 reference statements)
1
31
0
Order By: Relevance
“…Although these processes have been implicated in the pathogenesis of inflammatory bowel disease [14], they may also be beneficial by enhancing infant immune responses against HIV at the intestinal epithelium. Furthermore, it was recently suggested that HIV-intrinsic antisense anti–IL-15 micro-RNA is used by HIV to overcome IL-15–mediated immunity [15], further corroborating the protective role played by IL-15 against HIV.…”
Section: Discussionmentioning
confidence: 87%
“…Although these processes have been implicated in the pathogenesis of inflammatory bowel disease [14], they may also be beneficial by enhancing infant immune responses against HIV at the intestinal epithelium. Furthermore, it was recently suggested that HIV-intrinsic antisense anti–IL-15 micro-RNA is used by HIV to overcome IL-15–mediated immunity [15], further corroborating the protective role played by IL-15 against HIV.…”
Section: Discussionmentioning
confidence: 87%
“…FMRP is an RNA-binding protein that is implicated in protein synthesis and miRNA processing. Thus HIV could use HAAmiRNA to deregulate the host miRNA mechanism to dispose the virus by depleting FMRP ( [56] and references therein.) Although the existence of these HAAmiRNAs has not been proven, it is tempting to speculate that, in accordance with other viruses, HIV encodes miRNAs allowing HIV to survive in the host.…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…Here we propose that a specific region of the Hap antisense gene located within the HIV-1 long terminal repeat (LTR) is contributing to the programmed cell death or apoptosis observed with HIV infection (Ludwig, et al, 2006;Ludwig, 2008). Hap RNA initiates in the repeat (R) region of the HIV-1 provirus and is transcribed in the reverse direction (antisense) to the other HIV genes, overlapping the beginning portion of TAR region DNA, the TATA box, the SP1 sites and NFKb sites controlling HIV-1 sense transcription, as well as 200 nucleotides of the 3' end of the nef gene ( Figure 1B) (Ludwig, et al, 2006;Ludwig, 2008). The introduction of this antisense gene into human cells induced programmed cell death or apoptosis, as classically defined (Kerr, et al, 1972;Clarke, et al, 1993;Schwartz and Osborne, 1993;Cohen, 1993).…”
Section: Introductionmentioning
confidence: 99%